Constructing the bundle sheath towards enhanced photosynthesis. (19th February 2020) - Singh, Pallavi; Reeves, Gregory
Abstract : This article comments on: van Rooijen R, Schulze S, Petzsch P, Westhoff P . 2020. Targeted misexpression of NAC052, acting in H3K4 demethylation, alters leaf morphological and anatomical traits in Arabidopsis thaliana . Journal of Experimental Botany 71, 1434–1448 .